Panelist Acceptance Level Based on Sensory Tests on Cakalang Fish Noodle Products - Jufrin Pagune; Asriani I. Laboko; Asniwati Zainuddin; Nurbanilah Ahaya (International Journal of Applied Research and Sustainable Sciences, 2023)
The aim of the study was to determine the level of panelists' acceptance of skipjack noodle products by means of a sensory test by adding cakalang fish. The research was conducted using a sensory test with 50 panelists on noodle products with the addition of cakang fish. Observational parameters observed in this study are test regularly sensory in terms of color, aroma, taste, and texture. The results of the sensory test research show that the best results from the test color in sample 2 with a score of 50 (yellow), while in sample 1 with a score of 42 (bright white) and followed by a pale color with a score of 5 and (white and yellow) with a score of 3 in sample 1. The scent that the panelist likes the most in sample 1 (scent of flour) with a score of 50, while in sample 2 with a score of 30 (smell of spices), and followed by (scent of cakalang fish) with a score of 20. Taste test which was preferred by panelists in sample 1 with a score of 50 (taste of flour) and in sample 2 panelists chose more (taste of spices) with a score of 20 and (taste of flour) with a score of 15 and (taste of skipjack tuna) with a score of 15. Texture test on sample 1 with a score of 50 (noodle texture) and sample 2 with a score of 50 (noodle texture). The occurrence of panelists' preference for the texture of skipjack tuna noodles was caused by the gluten content